2022
DOI: 10.1080/13880209.2022.2042327
|View full text |Cite|
|
Sign up to set email alerts
|

Senkyunolide A inhibits the progression of osteoarthritis by inhibiting the NLRP3 signalling pathway

Abstract: Context Osteoarthritis (OA) is a degenerative disease. Senkyunolide A (SenA) is an important phthalide from Ligusticum chuanxiong Hort (Umbelliferae) with anti-spasmodic and neuroprotective effects. Objective We explored the effect of SenA on IL-1β-stimulated chondrocytes and OA mice Materials and methods Chondrocytes were stimulated by IL-1β (10 ng/mL) to establish an OA model in vitro . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…20 Nobiletin, tangeretin, senkyunolide A, glycyrrhetinic acid, and protocatechuate have been shown to have anti-inflammatory and antioxidant effects. [32][33][34][35] Curcumin and demethoxycurcumin have been shown to inhibit inflammation and apoptosis of nucleus pulposus cells, and delay intervertebral disc degeneration. 36,37 In various cell lines, curcumin treatment was reported to decrease CCL2 production.…”
Section: Discussionmentioning
confidence: 99%
“…20 Nobiletin, tangeretin, senkyunolide A, glycyrrhetinic acid, and protocatechuate have been shown to have anti-inflammatory and antioxidant effects. [32][33][34][35] Curcumin and demethoxycurcumin have been shown to inhibit inflammation and apoptosis of nucleus pulposus cells, and delay intervertebral disc degeneration. 36,37 In various cell lines, curcumin treatment was reported to decrease CCL2 production.…”
Section: Discussionmentioning
confidence: 99%
“…In the SX mixture, SEA was identified as a key molecule that significantly downregulated the expression of the tumor necrosis factor (TNF)-α-induced CD137, which is a member of the TNF receptor superfamily associated with increased plaque necrosis, macrophage infiltration, and decreased collagen content in the progression of unstable atherosclerotic plaques [55][56] . In a study using an osteoarthritis mouse model, SEA treatment was found to alleviate osteoarthritis progression by inhibiting the expression of multiple inflammatory cytokines and the NLRP3 signaling pathway [57] . Several studies have reported the anti-inflammatory effects of SEA in different cell models, via blocking the release of IL-1βinduced pro-inflammatory mediator nitric oxide (NO), inhibiting the expression of nod-like receptor family pyrin domain-containing 3, and downregulating the expression of inflammatory cytokines (IL-1β, IL-6, TNF-α) and chemokines (C-C motif chemokine ligand 20) [57][58] .…”
Section: Inhibition Of Inflammatory Reactionmentioning
confidence: 99%
“…In a study using an osteoarthritis mouse model, SEA treatment was found to alleviate osteoarthritis progression by inhibiting the expression of multiple inflammatory cytokines and the NLRP3 signaling pathway [57] . Several studies have reported the anti-inflammatory effects of SEA in different cell models, via blocking the release of IL-1βinduced pro-inflammatory mediator nitric oxide (NO), inhibiting the expression of nod-like receptor family pyrin domain-containing 3, and downregulating the expression of inflammatory cytokines (IL-1β, IL-6, TNF-α) and chemokines (C-C motif chemokine ligand 20) [57][58] .…”
Section: Inhibition Of Inflammatory Reactionmentioning
confidence: 99%
“…Recent pharmacological studies have shown that the active ingredients in the EF–CR pair, namely icariin, epimedin A, epimedin B, epimedin C, icariside I, icariside II, ligustilide, ferulic acid and senkyunolide A, exert anti‐inflammatory and analgesic effects via the modulation of various inflammatory factors and pathways (Du et al, 2021; Lai et al, 2013; Li et al, 2018; Shao et al, 2022; Wang et al, 2020; Zeng et al, 2017; Ziadlou et al, 2019; Zu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%